Volume 3: Operations, Monitoring, and Maintenance; Materials and Joining 2020
DOI: 10.1115/ipc2020-9589
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Establishing Manufacturing Process and Vintage of Line Pipe Using In-Situ Nondestructive Examination and Historical Manufacturing Data

Abstract: The October 2019 revisions to US federal rules governing natural gas pipelines require Operators to establish vintage and manufacturing process for line-pipe assets with incomplete records. Vintage and manufacturing process are considerations when establishing populations of pipe for maximum allowable operating pressure (MAOP) reconfirmation, materials verification, and integrity management programs. Additionally, the rule changes establish an allowance to utilize in-situ nondestructive examination (NDE) techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Equation (1) applies only for low-carbon ferrite-pearlite steels, and the reported accuracy of Equation (1) was ±31 MPa (4.5 ksi). Both manganese and carbon increase UTS, as observed by the following relationship developed by the same authors, because carbon makes up 0.77 wt.% of the microstructural constituent, pearlite, where pearlite represents the percent pearlite observed via metallographic evaluation [19]: UTS(MPa) = 294 + 28Mn + 83Si + 3.85(pearlite) + 7.7d − 1 2 (2) Recent findings [23] have shown that, over the past 100 years, manganese content and the content of microalloying elements such as vanadium, titanium, niobium, chromium, and molybdenum in line pipe steels has tended to increase, while carbon content has tended to decrease. Therefore, these long-accepted empirical relationships in Equations ( 1) and (2) may not hold for some contemporary line pipe steels.…”
Section: Introductionmentioning
confidence: 87%
“…Equation (1) applies only for low-carbon ferrite-pearlite steels, and the reported accuracy of Equation (1) was ±31 MPa (4.5 ksi). Both manganese and carbon increase UTS, as observed by the following relationship developed by the same authors, because carbon makes up 0.77 wt.% of the microstructural constituent, pearlite, where pearlite represents the percent pearlite observed via metallographic evaluation [19]: UTS(MPa) = 294 + 28Mn + 83Si + 3.85(pearlite) + 7.7d − 1 2 (2) Recent findings [23] have shown that, over the past 100 years, manganese content and the content of microalloying elements such as vanadium, titanium, niobium, chromium, and molybdenum in line pipe steels has tended to increase, while carbon content has tended to decrease. Therefore, these long-accepted empirical relationships in Equations ( 1) and (2) may not hold for some contemporary line pipe steels.…”
Section: Introductionmentioning
confidence: 87%